Nano selenium in broiler feeding: physiological roles and nutritional effects - Babak Hosseintabar-Ghasemabad; Olga Vilorievna Kvan; Elena Vladimirovna Sheida; Artem Vladimirovich Bykov; František Zigo; Alireza Seidavi; Mona Mohamed Mohamed Yasseen Elghandour; Moises Cipriano-Salazar; Maximilian Lackner; Abdelfattah Zeidan Mohamed Salem (AMB Express)
Abstract Using nanotechnology, while improving the health of broiler chickens, it is possible to control and reduce the conflict of minerals in the intestines, and toxicity of and pollution by these elements. It could be shown that the antioxidant and immune modulation effects of nano selenium are significantly superior compared to other sources of selenium. In addition, improving the quality of meat products with the use of nano selenium has promising results in the future perspective of quality improvement and food safety. Nutrition of permitted and optimal levels is very important in the consumption of nano selenium form and as it can have significant beneficial functional and health effects, in case of errors in the selected levels and doses, irreparable side effects and adverse results can occur. In this review report, an attempt has been made to introduce the position and importance of selenium and the approach of smart consumption of its nano form in the nutrition of broiler chickens. The novelty of using nanotechnology in feeding broiler chickens can be a unique opportunity to improve the bioavailability of important and rare elements such as selenium.